Coupling Compost from Chicken Manure and Inorganic Fertilizer to Improve Cassava (Manihot esculenta Crantz) Growth and Yield on a Ferralitic Soil in Côte d’Ivoire - Kouakou Marius Konan; Sifolo Seydou Coulibaly; Kouadio Ignace Kouassi; Bi Irié Arsène Zoro; Dénezon Odette Dogbo (Turkish Journal of Agriculture: Food Science and Technology)
This study aimed to evaluate the effect of compost from chicken manure, NPK fertilizer and the mixture of both fertilizers on agronomic parameters of four varieties of cassava (Yacé, Bonoua, Six mois and Alleda agba) in Côte d’Ivoire. The field experiment was carried out under a randomized complete block design with three replicates on a ferralitic soil during two season-cycles. The results showed that the different fertilizers stimulated plants growth and tuberous roots production. The highest number of stems (3) and leaves (66) was obtained with the mixture of NPK and compost applied on the variety “Bonoua”. All varieties that received the compost mixed with NPK produced more leaves with a dominance of the Bonoua variety (65.57). The highest number of tuberous roots (5.58), the heaviest weight per root (6.13 kg) and the highest yield (61.37 t/ha) were obtained while using the mixture of compost and NPK as fertilizer and “Bonoua” as variety. Thus, mixing compost from chicken manure and NPK can be recommended to improve cassava productivity in Côte d'Ivoire on a ferralitic soil.